Range finding test and measurement of wet weight and dry weight of Vetiveria zizanioides as an initial stage of phytoremediation of soil contaminated with used lubricants - Tangahu, Bieby Voijant; Winata, Alif Yoga; Arliyani, Isni (Plant Science Today, 2022)
Environmental pollution caused by the development of industry and the rapid increase in the number of vehicles currently requires restrictions on the use of lubricants. Used lubricants contain complex mixtures of hydrocarbons that adversely affect plants by creating conditions that make essential nutrients such as nitrogen and oxygen needed for plant growth unavailable and cause severe problems in soil ecosystems and the rhizosphere. The accumulation of these spills can complicate the degradation process by microorganisms in the soil. Vetiver (Vetiveria zizanioides) can grow at various levels of nutrients and insufficient abiotic conditions, so it is used in multiple studies as a hyperaccumulator plant. Preliminary research in determining the concentration of used lubricant handled by the vetiver can be determined through the Range Finding Test (RFT) stage. RFT is the stage of observing the plant's ability to maintain its life while degrading pollutants. Physical observations and laboratory analysis determine how strong the plants live in media contaminated with used lubricant pollutants. The results showed that vetiver could live in an environment contaminated with used lubricants with a concentration of up to 4% of the total mass of the media (40 ppm). Sample C2 had an average growth rate of 0.481 cm/day with a root elongation ratio of 0.333. The average dry fraction of plant leaves is 0.602 and the root is 0.372.